Genetically engineered insects with sex-selection and genetic incompatibility enable population suppression - Upadhyay, Ambuj; Feltman, Nathan R; Sychla, Adam; Janzen, Anna; Das, Siba R; Maselko, Maciej; Smanski, Michael (eLife, 2022)
Engineered Genetic Incompatibility (EGI) is a method to create species-like barriers to sexual reproduction. It has applications in pest control that mimic Sterile Insect Technique when only EGI males are released. This can be facilitated by introducing conditional female-lethality to EGI strains to generate a sex-sorting incompatible male system (SSIMS). Here, we demonstrate a proof of concept by combining tetracycline-controlled female lethality constructs with a pyramus-targeting EGI line in the model insect Drosophila melanogaster. We show that both functions (incompatibility and sex-sorting) are robustly maintained in the SSIMS line and that this approach is effective for population suppression in cage experiments. Further we show that SSIMS males remain competitive with wild-type males for reproduction with wild-type females, including at the level of sperm competition.
Keywords: genetic biocontrol; insect biotechnology; population suppression; engineered genetic incompatibility